2005
DOI: 10.1097/00001756-200501190-00008
|View full text |Cite
|
Sign up to set email alerts
|

NPY neurons express somatostatin receptor subtype 1 in the arcuate nucleus

Abstract: The regulation of growth hormone (GH) secretion involves hypothalamic somatostatin and its specific receptors (sst1-sst5). sst1 is highly expressed in the arcuate nucleus (AN), and several data suggest that sst1 receptors are preferentially involved in the somatotropic hypothalamic network. Neuropeptide Y (NPY)-containing neurons function as direct transducers for GH feedback. Interestingly, there is an overlap in the distribution of NPY and sst1 containing cells in the AN. To determine whether these NPY cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…2003). These results, together with the observation that a fraction of orexigenic NPY neurons in the ARC co‐express sst1 (Fodor et al . 2005) has led to the hypothesis that somatostatin may affect the leptin‐mediated regulation of energy homeostasis.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…2003). These results, together with the observation that a fraction of orexigenic NPY neurons in the ARC co‐express sst1 (Fodor et al . 2005) has led to the hypothesis that somatostatin may affect the leptin‐mediated regulation of energy homeostasis.…”
supporting
confidence: 57%
“…2000). In addition, orexigenic NPY‐neurons, which were recently shown to co‐express sst1 (Fodor et al . 2005), project inhibitory collaterals to anorexigenic POMC‐neurons (Cowley et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our last study on anatomical connections between NPY and somatostatin neurons demonstrated such links in prepubertal lambs on the levels of PEV and ARC nuclei (unpublished). The direct interactions between the somatostatin and NPY in the area of ARC nuclei were found in rats where approximately 7% of NPY perikarya coexpressed the specific receptor for somatostatin -sst1 [42].These data suggest that there is an anatomical basis for interactions between these two groups of cells and that NPY neurons can influence the secretion of GH by influencing hypothalamic somatostatin neurons.…”
Section: Neuropeptide Ymentioning
confidence: 76%
“…The stimulatory action of SRIH on GHRH neuronal activity may be mediated via sst1 because infusion of antisense sst1 oligonucleotides suppresses GH release, while antisense sst2 oligonucleotides have no effect [43]. It should also be noted that a recent report suggests NPY neurons, within the arcuate nucleus of rats, may also be targets of direct SRIH regulation, since a subpopulation of these neurons expresses sst1 [44]. …”
Section: Discussionmentioning
confidence: 99%